Evaluation of Antidepressant-like Effect of Olax Subscorpioidea Oliv. (Olacaceae) Extract in Mice - Adeoluwa, O. A.; Aderibigbe, A. O.; Bakre, A. G. (Drug Research, 2015)
Olax subscorpioidea is a shrub or tree found in Nigeria, and other parts of Africa. It is indicated in the management of inflammatory disorder, mental illness, convulsion, pain, and cancer.Based on the folkloric use in the management of mental illness, antidepressant activity of Olax subscorpioidea (6.25–50 mg/kg, i. p.) was investigated using forced swimming, tail suspension, yohimbine induced lethality and reserpine induced depression tests.The results showed that, Olax subscorpioidea produced significant dose dependent reduction in immobility time in forced swimming [F (5, 24)=17.22, p<0.0001] and tail suspension [F (5, 24)=14.94, p<0.0001] tests without causing changes in locomotor activity in open field test. It was also found that Olax subscorpioidea significantly reduced diarrhea in reserpine model of depression [F (5, 24)=10, p<0.0001]. None of the doses potentiated yohimbine induced lethality in mice. In conclusion Olax subscorpioidea possessed antidepressant action, thus justifying its use in the management of mental illness.
Keywords: antidepressant; mental illness; immobility; Olax subscorpioidea; yohimbine